Condições históricas e sociais das apropriações de Maria Firmina dos Reis e sua “obra” (1973-2022) - MENDES, Melissa Rosa Teixeira (2023)
This thesis focuses on analyzing the discourses about the 19th century Maranhão writer Maria Firmina dos Reis (1825-1917) and her writings, considering that in recent decades there has been an increase in laudatory productions, mainly in academic domains. We examine how the recent consecration of "woman", "writer" and "black" is linked to the emergence of gender and ethnic-racial issues, especially to the affirmation of feminist and black movements. To this end, we sought to: 1) trace the conditions for the emergence of discourses, between the periods from 1973 to 2022, based on a procedural analysis of social and historical events that, in Brazil and in the world, enabled the emergence of new perspectives understanding themselves and their history, seeking a new writing of identities for women, blacks and black women, especially from the 1970s onwards; 2) reconstruct, through newspapers of the time, the documentary sources left by the writer/teacher, such as her Album and her texts such as short stories and the novel, the trajectory of Maria Firmina dos Reis, aligned with the Brazilian historical period in which she lived and produced her cultural goods; 3) based on the survey of information about the life and work of Maria Firmina dos Reis and in the Brazilian and world social and historical context between the years 1970 to 2022, to understand the discourses about Maria Firmina, demonstrating the hypothesis that social changes and historical processes, according to the sociology of Norbert Elias, are essential for understanding the configurations and reconfigurations in the processes of struggles for new discourses, new identities, and the rewriting of the history of a group. Following the research agenda of the Laboratory for the Study of Political and Cultural Elites (LEEPOC) at the Federal University of Maranhão, we gathered historical, documental, bibliographical and biographical information to examine Firmina's trajectory and the appropriations/constructions about the "author" and his “work”. Although there is currently a great diversity of works in the academic domains about Maria Firmina dos Reis, we reinforce that this research specifically analyzes these academic works and their expressive multiplicity.